Evaluation of outpatient services in the Brazilian Unified National Health System for persons living with HIV: a comparison of 2007 and 2010 - Loch, Ana Paula (2018)
Health services play a crucial role in reaching the 90-90-90 target of controlling the HIV epidemic. This study evaluates the organization of Brazilian health services in improving, monitoring, and retention in HIV care and adherence support. Percentage variation (PV) was used to compare the responses by services to an evaluation questionnaire on organizational quality (Qualiaids) in 2007 and 2010. The study analyzed the 419 services that completed the questionnaire in 2007 (83.1% of respondents) and 2010 (63.6%). Management actions of retention and support although increased in the period, but remained at low rates, for example: systematic meetings for case discussion (32.7% in 2010; PV = 19.8%) and recording of missed medical appointments (35.3%; PV = 36.8%). Patient care actions related to adherence to ART remained largely exclusive to the attending physician. The supply of funds and resources from the Federal Government (medicines and specific HIV tests) remained high for the vast majority of the services (similar to 90%). It will not be possible to achieve a significant decrease in HIV transmission as long as retention in treatment is not a priority in all the health services.